Factors influencing regional epidemiology of strongyle nematodes at organized sheep farms in Rajasthan - SWARNKAR, C P; SINGH, D; KHAN, F A (The Indian Journal of Animal Sciences, 2020)
A study was conducted to observe the influence of year, season, month, breed, age and sex on epidemiology of strongyle nematodes in different sheep breeds managed at organised farms in arid and semi-arid Rajasthan by evaluating 14,030 fresh faecal samples (from April 2016 to March 2019). The overall incidence of strongyle worms was significantly higher (74.1%) in semi-arid as compared to 27.4% in arid region. Among breeds, it varied from 25.6% in Magra to 74.8% in Malpura sheep. The effect of year was significant on regional as well breed-wise incidence. Season had significant effect on regional incidence with maximum incidence during monsoon. A significant breed variation in overall and seasonal incidence was found only in arid region. Irrespective of sheep breed, significantly higher incidence of strongyle worms was observed in adult sheep in both the regions. Male had significantly higher incidence of strongyle worms in both the regions. The effect of agro-climatic region was significant on overall intensity of strongyle worms with mean FECs of 117.8±3.7 epg in arid and 1098.9±45.2 epg in semi-arid region. Breed-wise, the effect of year on intensity of strongyle nematodes was significant in arid region only. Seasonal intensity was significantly higher during monsoon season in both the agro-climatic regions and in all the breeds. Effect of age on overall intensity of infection was also significant in both the regions with higher mean FECs in adult animals as compared to young ones. In both the regions, males possessed higher FECs as compared to females. On coproculture, Haemonchus contortus, Trichostrongylus sp and Oesophagostomum sp were recovered with maximum (71.1±2.1%) mean annual proportion of H. contortus. Availability of infective larvae of GI nematodes on herbage was observed during monsoon and extended up to post-monsoon season in semi-arid region. Comparatively higher herbage infectivity was not noticed in semi-arid farm with a peak of 2,100.0±97.9 L3/kg dry matter of herbage in September. The study suggest a marked influence of agro-climatic region on epidemiology and dynamics of strongyle nematodes in sheep flocks and on pasture. The breed variation was evident only in arid conditions. Further, the magnitude of monthly intensity of strongyle infection in arid region suggested anthelmintics intervention through targeted selective approach instead of strategic en-mass drench.